Penerapan Model Snowball Throwing untuk Meningkatkan Hasil Belajar Pada Operasi Bilangan Pecahan Di SMP 1 Islam Jember - Dewi Sekar Melati Ifitifiani; Toto’ Bara; Tri Susilaningtyas (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2017)
Learning outcomes are reflected in the personality of students in the form of changes in behavior after experiencing the learning process. Learning outcomes describe the abilities of students in cognitive, affective and psychomotor aspects. Snowball Throwing learning model is an effective way to change learning patterns in the classroom. The Snowball Throwing learning model is an effective way to change learning patterns in the classroom. The Snowball Throwing learning model gives students the opportunity to work alone and work with teams. Snowball Throwing Model to Improve Learning Outcomes of Operation Numbers for Fractions of Grade VII Students of Islamic Jember 1 Middle School with 27 students. Based on the research results obtained by learning cycle I = 3.70% complete. Cycle II = completely 100% using the Snowball Throwing learning model. Thus an increase in student learning outcomes in the second cycle of the Fractional Numbers operation material using the Snowball Throwing model for students of class VII B in Islamic Junior High School 1.Keywords : Snowball Throwing, Learning Outcomes